2022
DOI: 10.5194/hess-26-2939-2022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of post-processing medium-range ensemble streamflow forecasts from the European Flood Awareness System

Abstract: Abstract. Streamflow forecasts provide vital information to aid emergency response preparedness and disaster risk reduction. Medium-range forecasts are created by forcing a hydrological model with output from numerical weather prediction systems. Uncertainties are unavoidably introduced throughout the system and can reduce the skill of the streamflow forecasts. Post-processing is a method used to quantify and reduce the overall uncertainties in order to improve the usefulness of the forecasts. The post-process… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 81 publications
1
6
1
Order By: Relevance
“…According to the EA documentation (EA, 2021), the gauge metadata includes a Typical High water-level threshold set to the 95th percentile of all the water levels measured at that gauge since its installation. This threshold was chosen as the flood threshold in this work as it was available for most of our gauges, and as percentile thresholds are regularly used to evaluate peak discharge (Matthews et al, 2022). When this threshold was not available as metadata (e.g., gauges in the Republic of Ireland), if a camera was associated with this gauge, it was removed for this specific experiment.…”
Section: Methodsmentioning
confidence: 99%
“…According to the EA documentation (EA, 2021), the gauge metadata includes a Typical High water-level threshold set to the 95th percentile of all the water levels measured at that gauge since its installation. This threshold was chosen as the flood threshold in this work as it was available for most of our gauges, and as percentile thresholds are regularly used to evaluate peak discharge (Matthews et al, 2022). When this threshold was not available as metadata (e.g., gauges in the Republic of Ireland), if a camera was associated with this gauge, it was removed for this specific experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Both observations and forecasts contain uncertainties and systematic errors. To improve forecasts by reducing uncertainties and errors, statistical or ML‐type methods can be applied to both the incoming meteorological variables, such as temperature, evaporation, or precipitation and the forecast outputs of hydrological variables, such as river discharge/streamflow, flood depth or extent (Khajehei & Moradkhani, 2017; Madadgar et al., 2014; Matthews et al., 2022; Wetterhall & Smith, 2019). These errors are considered in terms of different attributes of “forecast quality.”…”
Section: Riverine Floodmentioning
confidence: 99%
“…Presentations on the advances in pre-processing techniques were centred around increasing the skill of precipitation predictions (especially of intense and rare events) at subseasonal and In conclusion, the improvements brought by pre/post-processing techniques were conditioned on many factors: the catchments' characteristics ([GM-P]; Matthews et al, 2022), the hydrometeorological variable [AC-P], and the method implemented [FJ-P]. In fact, many presentations suggested that selecting suitable methods is rather application-dependent [WP-K; FT-P; WG-P; AB1-P].…”
Section: Reducing Uncertainty Via Hydrological Pre-/post-processingmentioning
confidence: 99%